2020
DOI: 10.7759/cureus.8421
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Injuries in Master Swimmers: A National Survey in Turkey

Abstract: Background This study aimed to determine the frequency of musculoskeletal injuries in master swimmers in Turkey. Methods A questionnaire was formed and distributed to all master swimmers registered with the Turkish Swimming Federation. The collected data included age, sex, the age to start swimming (SAS), weekly training time (WTT), weekly training distance (WTD), any painful episode that lasted more than 10 days in any of the body regions within last one year, any confirmed diagnosis of musculoskeletal diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…The most common site of injury was the shoulder (48 of 90 studied injuries). This is consistent with numerous studies indicating the high incidence of shoulder pain and pathologies among swimmers [2,3,5,7,9,10,[13][14][15][16][17][18][19][20]. Lower extremity injuries were most often localized to the knee (20 of 90 studied injuries).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The most common site of injury was the shoulder (48 of 90 studied injuries). This is consistent with numerous studies indicating the high incidence of shoulder pain and pathologies among swimmers [2,3,5,7,9,10,[13][14][15][16][17][18][19][20]. Lower extremity injuries were most often localized to the knee (20 of 90 studied injuries).…”
Section: Discussionsupporting
confidence: 87%
“…However, those with swimming-associated pain and a scoliosis diagnosis were included for analysis. Prior research has demonstrated that back pain is a common presenting complaint for swimmers [9,10,27]. Nyska studied four swimmers with low back pain and found that three specialized in "short-axis" swimming strokes -butterfly and breaststroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Back injuries are understood to be relatively common in swimmers and are thought to be from overuse. 1 , 13 Furthermore, overuse as well as excessive hyperextension has been indicated as a factor that predisposes swimmers to degenerative disk disease, spondylolysis, and spondylolisthesis. 24 As a result, it is not surprising that lumbar spine injuries were commonly observed in our series.…”
Section: Discussionmentioning
confidence: 99%
“…Publications have cited a generally high injury prevalence in UWR, 16 as well as specific injuries in UWR—for example, hamate fractures of the ball-carrying hand 1 , 14 , 22 and an increased incidence of back pain. 11 Atilla et al 2 characterized injuries of master swimmers by using a questionnaire for athletes. This method appeared useful to provide an overview of injuries in a sport and was used as such in this study of UWR.…”
mentioning
confidence: 99%